Structural Basis for Transcript Elongation Control by NusG Family Universal Regulators - Kang, Jin Young; Mooney, Rachel Anne; Nedialkov, Yuri; Saba, Jason; Mishanina, Tatiana V.; Artsimovitch, Irina; Landick, Robert; Darst, Seth A. (Cell, 2018)
NusG/RfaH/Spt5 transcription elongation factors are the only transcription regulators conserved across all life. Bacterial NusG regulates RNA polymerase (RNAP) elongation complexes (ECs) across most genes, enhancing elongation by suppressing RNAP backtracking and coordinating ρ-dependent termination and translation. The NusG paralog RfaH engages the EC only at operon polarity suppressor (ops) sites and suppresses both backtrack and hairpin-stabilized pausing. We used single-particle cryoelectron microscopy (cryo-EM) to determine structures of ECs at ops with NusG or RfaH. Both factors chaperone base-pairing of the upstream duplex DNA to suppress backtracking, explaining stimulation of elongation genome-wide. The RfaH-opsEC structure reveals how RfaH confers operon specificity through specific recognition of an ops hairpin in the single-stranded nontemplate DNA and tighter binding to the EC to exclude NusG. Tight EC binding by RfaH sterically blocks the swiveled RNAP conformation necessary for hairpin-stabilized pausing. The universal conservation of NusG/RfaH/Spt5 suggests that the molecular mechanisms uncovered here are widespread. [Display omitted] •Cryo-EM structures of NusG and RfaH-bound transcription elongation complexes•NusG and RfaH suppress backtracking by stabilizing the upstream duplex DNA•RfaH recognizes an ops DNA hairpin in the nontemplate strand of the transcription bubble•RfaH suppresses RNA hairpin-stabilized pausing by preventing RNAP swiveling NusG/Spt5 transcription elongation factors are the only transcription regulators conserved across all domains of life, assisting RNA polymerase elongation and linking the transcription complex to additional accessory factors genome wide. Cryo-electron microscopy structures of bacterial transcription complexes with NusG or its operon-specific paralog RfaH suggest NusG/RfaH inhibit backtrack pausing by stabilizing the upstream duplex DNA following the transcription bubble. RfaH further supresses pausing and termination by preventing RNA-hairpin induced swiveling, an RNA polymerase conformational change associated with pausing.